Les défis et les enjeux liés au maintien à domicile des aînés: une étude de cas en milieu urbain néo-brunswickois - Dupuis-Blanchard, Suzanne; Simard, Majella; Gould, Odette; Villalon, Lita (Université de Moncton, 2011)

L'influence du contexte sociolinguistique minoritaire sur le maintien à domicile des aînés en milieu rural dévitalisé : le cas d’Acadieville au Nouveau-Brunswick - Simard, Majella; Dupuis-Blanchard, Suzanne; Villalon, Lita; Gould, Odette; Ethier, Sophie; Gibbons, Caroline (La Revue canadienne du vieillissement, 2015)
New Brunswick is one of the provinces most affected by the aging of the population. Moreover, aging at home in Francophone minority communities is a major challenge in rural areas. The goal of this paper is to identify the main advantages and disadvantages of aging at home and to expose organizational strategies deployed by seniors and their families in order to promote aging in place. The case study is the method of analysis that we have recommended. Our methodology is based on content analysis of 13 semi-structured interviews with seniors and their children. The results show that family and community support, resourcefulness and resiliency, the practice of leisure activities as well as the living environment are among the principal means used by older adults to promote aging at home.